SOSIALISASI KEPADA MASYARAKAT DENGAN PENYAKIT TIDAK MENULAR (HIPERTENSI DAN DIABETES MELITUS) DALAM PENCEGAHAN COVID -19 DI KELURAHAN MEDONO KOTA PEKALONGAN - Tri Anonim; Suryo Pratikwo; Rosmiati Saleh; Sumarni Sumarni (Poltekkes Kemenkes Semarang, 2021)
AbstractSince the Covid-19 case was first reported in Indonesia to date, the number of positive cases has always increased, including the number of deaths. The transmission is increasingly widespread, while public awareness of health protocols is still lacking. This condition has led to various countermeasures by the governments of various countries, including Indonesia. However, the efforts made will not be effective if it is not supported by the wider community. Covid-19 patients can experience severe and aggravating symptoms if accompanied by co-morbidities. Some comorbidities that can worsen to cause death in Covid-19 patients: hypertension, diabetes, lung disease, heart disease. Objective: increase participants' knowledge about preventing the transmission of Covid-19 and improve skills in implementing health protocols. Methods: provide education, information, demonstration. Result: increased target knowledge and skills. Conclusion: the increase in target knowledge is evidenced by the average pre-test score of participants from 72.08 (good enough) to 81.4 (good) in the post-test, and increased skills in implementing clean and healthy living behaviors, especially health. protocol. Suggestion: To prevent the transmission of Covid-19, patients with hypertension and diabetes mellitus are expected to be disciplined in implementing health protocols, consuming balanced nutritious foods containing high anti-oxidants, stopping smoking, and delaying traveling to areas with high numbers. coronavirus caseÂ Keywords: Hypertension, Diabetes Mellitus, Covid-19